The effect of customer experience, place attachment, customer satisfaction, and word-of-mouth on revisit intention - Rahmatullah, Arwin Yafi (Journal of Management and Business Insight, 2024)
Purpose-E-commerce companies need to pay attention to the level of revisit intention on the services they provide. This ensures that their services can pay attention to consumer loyalty to continue making transactions on the service. This study aims to analyze the effect of customer experience, place attachment, customer satisfaction, and word-of-mouth on revisit intention for active users of Shopee e-commerce in Indonesia. Design/Methodology/Approach-This study analyzes revisit intention in active users of Shopee e-commerce in Indonesia. The sample of this study consisted of 130 respondents. Research data was collected using an online questionnaire with a Likert scale. Data analysis was done using SPSS version 25 to test validity, reliability, and research hypothesis testing. Findings-This study proves that all four hypotheses were accepted or supported. Customer experience, place attachment, customer satisfaction, and word-of-mouth are each partially proven to affect revisit intention positively. These four factors can increase consumers’ intention to revisit Shopee e-commerce sites in online buying and selling transactions. Research limitations/implications-The results of this study can be used as a reference for e-commerce companies to improve consumers’ revisit intentions. Revisit intention is essential for e-commerce companies to maintain consumer loyalty and attract new consumers to buy and sell transactions through e-commerce. Originality/value-There is no research on revisit intention that uses similar variables as in this study. Previous research analyzed factors that were different from those in this study. In addition, previous studies used objects in e-commerce that differed from this study.